PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS PELANGGAN DI APOTEK PANJI FARMA - Monik Krisnawati (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2019)
Maintaning customers must be a top priority for pharmacies rather than utilizing new customers. One of the pharmacy strategies in maintaining is providing services according to needs and maintaining good relationships with customers so that customer loyalty will be created. The purpose of this study was to determine and analyze the influence of customer identification factors, customer differentiation, customer interaction, custumization on customer loyalty of the Panji Farma Pharmacy and find out the most dominant factors affecting the loyalty of the customers of Panji Farma Pharmacy. This study included a type of quantitative descriptive research with a survey approach. Data collection in this study using non randomg sampling techniques (non probability sampling) with samping methods using accidental sampling. The analysis used is multiple linear regression analysis. Based of the results of data analysis, information is obtained that calculated Fcount is 17,094 greater than F table 2,51. It shows that the customer identification factor, customer differentiation, customer interaction, customization has a significant effect on customer loyalty at the Panji Farma Pharmacy. Of the four factors it is known that the customer differentiation factor (X2) has the most dominant influence compared to the other three factors. It can be seen from the value of tcount for the customer differentiation factor is 3,203 at most than the value of t calculated for the customer identification factor (X1) 2,288, customer interaction (X3) 2,775 and customization (X4) 2,288. This study provides the conclusion that customer identification factor, customer differentiation, customer interaction, customization have a significant influence on customer loyalty and customer differentiation factor is the most dominant factor in customer loyalty at the Panji Farma Pharmacy.